Synaptic Plasticity, Metaplasticity and Depression - R. Vose, Linnea; K. Stanton, Patric (Current Neuropharmacology, 2017)
The development of a persistent depressive affective state has for some time been thought to result from persistent alterations in neurotransmitter-mediated synaptic transmission. While the identity of those transmitters has changed over the years, the literature has lacked mechanistic connections between the neurophysiological mechanisms they regulate, and how these mechanisms alter neuronal function, and, hence, affective homeostasis. This review will examine recent work that suggests that both long-term activity-dependent changes in synaptic strength (“plasticity”), and shifting set points for the ease of induction of future long-term changes (“metaplasticity”), may be critical to establishing and reversing a depressive behavioral state. Activitydependent long-term synaptic plasticity involves both strengthening and weakening of synaptic connections associated with a dizzying array of neurochemical alterations that include synaptic insertion and removal of a number of subtypes of AMPA, NMDA and metabotropic glutamate receptors, changes in presynaptic glutamate release, and structural changes in dendritic spines. Cellular mechanisms of metaplasticity are far less well understood. Here, we will review the growing evidence that long-term synaptic changes in glutamatergic transmission, in brain regions that regulate mood, are key determinants of affective homeostasis and therapeutic targets with immense potential for drug development.
Keywords: synaptic plasticity